An Irish Howl. - (:unkn) unknown (Whittle, J., 1799)
Scholarly notes may be added at a later date.
1 print : col.
Keywords: Caricatures; Cartoons; Ireland -- Politics and government -- 1760-1820; United Irishmen; Anti-Jacobin Review and Magazine